2018
DOI: 10.1002/adsc.201801007
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Approach on N‐Oxides in Gold Catalysis – A Case Study

Abstract: An extensive kinetic study of selected key reactions of (oxidative) gold catalysis concentrates on the decrease of the catalytic activity due to inhibition of the gold(I) catalyst caused by pyridine derivatives that are obtained as by-products if N-oxides are applied as oxygen donors. The choice of the examined pyridine derivatives and their corresponding N-oxides has been made regardless of their commercial availability; particular attention has been paid to the practical benefit which up to now has been negl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
40
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 53 publications
(43 reference statements)
0
40
0
1
Order By: Relevance
“…α-Oxo gold(I) carbenes can undergo several reaction pathways, including cyclopropanations, migrations, ring expansions, insertions, and reactions with nucleophiles. 7 …”
Section: Introductionmentioning
confidence: 99%
“…α-Oxo gold(I) carbenes can undergo several reaction pathways, including cyclopropanations, migrations, ring expansions, insertions, and reactions with nucleophiles. 7 …”
Section: Introductionmentioning
confidence: 99%
“…[42][43] The selection of the N-oxides was based on our recent work. [44] For the present study, we examined the efficient 8-methylquinoline N-oxide 6 a reagent, the fast-reacting 3,5-dibromopyridine N-oxide 6 b and pyridine N-oxide 6 c as reference compounds.…”
mentioning
confidence: 99%
“…Simple salts like AuCN, AuCl, and KAuBr 4 exhibited no catalytic activity (entry 12). A brief screening of counter anions [11] revealed that SbF 6 À and BF 4 À were much worse than NTf 2 À with regard to the reaction yield (entries 13,14). No further improvement was observed when screening at different temperatures (entries 15,16).…”
mentioning
confidence: 99%